(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article provides a theoretical and practical analysis of the role and significance of speech training in the correctional education of blind children. It examines the effects of speech-training sessions on speech development and explores the possibilities of integrating them with educational games and interactive methods. The article also substantiates effective techniques for improving pronunciation, expanding vocabulary, developing coherent speech, building communicative competence, and supporting the social adaptation of blind children through speech training. The research findings demonstrate that speech training is an important pedagogical technology for improving the effectiveness of corrective speech-therapy interventions.